Remote Embedded System for Agricultural Field Monitoring: Enhancing Resource Allocation in Agriculture - Ronald J. Contijo; Lucas C. de Camargo; Renan O. A. Takeuchi; André L. S. Moscato; Lafaiete H. R. Leme; Wenderson N. Lopes (Engineering Proceedings)
This research addresses the need to enhance agricultural management due to rapid population growth in the 20th and 21st centuries. It focuses on integrating sensors and embedded systems to collect data on soil and air conditions, including temperature, humidity, and solar radiation. This information is obtained using ESP32 microcontrollers and stored in a centralized database. This system uses JavaScript and the Leaflet library’s interpolation algorithm to create interactive maps, allowing the farmers in the northern region of Paraná, Brazil, to monitor their fields and activate irrigation according to the predefined routines. This innovative system provides a data-driven approach to agriculture and automated irrigation, conferring advantages to the farmers and their families.